2018
DOI: 10.1186/s13287-018-1060-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct role of autophagy on angiogenesis: highlights on the effect of autophagy in endothelial lineage and progenitor cells

Abstract: Autophagy plays a critical role in the dynamic growth of each cell through different conditions. It seems that this intracellular mechanism acts as a two-edged sword against the numerous cell insults. Previously, autophagy was described in the context of cell activity and behavior, but little knowledge exists related to the role of autophagy in endothelial cells, progenitors, and stem cells biology from different tissues. Angiogenic behavior of endothelial lineage and various stem cells are touted as an inevit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 184 publications
(207 reference statements)
0
49
0
1
Order By: Relevance
“…Apoptosis is triggered in ischemic tissues in order to remove damaged or unhealthy cells, accompanied by the repair of lost tissues via the active proliferation of the intact cell components. Autophagy, on the other hand, is an adaptive response to environmental stresses including nutrient starvation due to tissue destruction or blood shortage, and it seems to be also required for the development of vascular ECs [80]. Downregulation of BAG3 could represent an increase in apoptosis but reduced autophagy [79,81], mainly in the CACtreated mice, although further studies should confirm such hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…Apoptosis is triggered in ischemic tissues in order to remove damaged or unhealthy cells, accompanied by the repair of lost tissues via the active proliferation of the intact cell components. Autophagy, on the other hand, is an adaptive response to environmental stresses including nutrient starvation due to tissue destruction or blood shortage, and it seems to be also required for the development of vascular ECs [80]. Downregulation of BAG3 could represent an increase in apoptosis but reduced autophagy [79,81], mainly in the CACtreated mice, although further studies should confirm such hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the study of multiple differentiation capacity of distinct stem cells or progenitors could enable us in concomitant promotion of angiogenesis and cardiomyogenesis [26]. More than a decade, studies have suggested that different signaling pathways, such as autophagy, are involved to commence a novel cell-fate acquisition in different cell types [27]. Due to a lack of sufficient data, we reasoned that pharmacological modulation of autophagy (either stimulation or inhibition) in bone marrow-derived CD146 + cells would modulate the differentiation capacity and further change regenerative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study of multiple differentiation capacity of distinct stem cells or progenitors could enable us in concomitant promotion of angiogenesis and cardiomyogenesis [27]. More than a decade, studies have suggested that different signaling pathways, such as autophagy, are involved to commence a novel cell-fate acquisition in different cell types [28]. Due to a lack of sufficient data, we reasoned that pharmacological modulation of autophagy (either stimulation or inhibition) in bone marrowderived CD146 + cells would modulate the differentiation capacity and further change regenerative capacity.…”
Section: Discussionmentioning
confidence: 99%